Social Interactions and Crime revisited: An Investigation using Individual Offender Data in Dutch Neighborhoods - Wim Bernasco; Thomas de Graaff; Jan Rouwendal; Wouter Steenbeek (Tinbergen Institute, 2012)
Using data on the age, sex, ethnicity and criminal involvement of 14.3 million residents aged 10-89 residing in 4,007 neighborhoods in the Netherlands, this article tests whether an individual's decision whether or not to be involved in crime is affected by the number of criminals in the neighborhood. Controlling for unobserved neighborhood heterogeneity and endogeneity of this decision, a small positive effect is found on violent crime, but not on property crime. The results suggest that individual characteristics and other neighborhood characteristics play a much greater role in an individual's decision to be involved in crime.
urn:NBN:nl:ui:31-1871/38764
Keywords: R1; R2; 330; social interactions; neighborhoods; crime; Soziale Beziehungen; Kriminalität; Nachbarschaft; Niederlande